Heinabergsjökull and Skalafellsjökull, Iceland : active temperate piedmont lobe and outwash head glacial landsystem. - Evans, D.J.A.; Orton, C. (Journal of Maps, 2015)
A 1:15,000 scale map of the glacial geomorphology and surficial geology of the Heinabergsjökull and Skalafellsjökull glacier forelands in southeast Iceland depicts a landsystem imprint of actively receding temperate glaciers in a mountain terrain with a high glacifluvial sediment yield. The landsystem is characterised by the three diagnostic depositional domains for active temperate glacier systems (marginal morainic; subglacial; glacifluvial/glacilacustrine) together with site-specific landform-sediment assemblages indicative of jökulhlaup drainage from ice-dammed lakes. Other features are overridden moraines and fluted kame terraces, indicative of ice-marginal and glacifluvial palimpsests preserved beneath temperate glacier ice. A significant outwash head in front of Heinabergsjökull records the long-term accumulation of proglacial outwash and was responsible for a radical change in proglacial drainage patterns (topographically unrestricted to restricted) once the glacier snout had receded from the ice-contact face of the landform. The Heinabergsjökull/ Skalafellsjökull foreland constitutes a modern analogue for active temperate piedmont lobes associated with the construction of large outwash heads fed by high glacifluvial sediment yields. This is one of the most common glacial depositional scenarios associated with the more restricted, mountain-based, average glaciation style during a typical cold stage.